Do synthetic fragrances in personal care and household products impact indoor air quality and pose health risks? - Rádis-Baptista, Gandhi (2023)
Fragrance compounds (synthetic fragrances or natural essential oils) comprise formulations of specific combinations of individual materials or mixtures. Natural or synthetic scents are core constituents of personal care and household products (PCHPs) that impart attractiveness to the olfactory perception and disguise the unpleasant odor of the formula components of PCHPs. Fragrance chemicals have beneficial properties that allow their use in aromatherapy. However, because fragrances and formula constituents of PCHPs are volatile organic compounds (VOCs), vulnerable populations are exposed daily to variable indoor concentrations of these chemicals. Fragrance molecules may trigger various acute and chronic pathological conditions because of repetitive human exposure to indoor environments at home and workplaces. The negative impact of fragrance chemicals on human health includes cutaneous, respiratory, and systemic effects (e.g., headaches, asthma attacks, breathing difficulties, cardiovascular and neurological problems) and distress in workplaces. Pathologies related to synthetic perfumes are associated with allergic reactions (e.g., cutaneous and pulmonary hypersensitivity) and potentially with the perturbation of the endocrine-immune-neural axis. The present review aims to critically call attention to odorant VOCs, particularly synthetic fragrances and associated formula components of PCHPs, potentially impacting indoor air quality and negatively affecting human health.